Vulnerabilità, morte e pietas. L’atto della sepoltura e le sue implicazioni giuridiche (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Una chiarificazione concettuale - 2. Vulnerabilità e diritto - 3. L’atto della sepoltura - 4. Il diritto alla sepoltura - 5. Conclusioni.Vulnerability, Death and Pietas. The Act of Burial and its Legal ImplicationsABSTRACT: This paper offers a conceptual clarification of the concept “vulnerability”, focusing in particular on the legal meanings it has recently assumed. Considering the cultural legacy relative to the act of burial, the reflection will also lead to put at stake, through the vulnerability’s perspective, the need for a harmonization and an updating of the legislation referred to cemeteries and sepulchres.